Can Occupational Stress be Reduced by Gamification? A Study of Newcomers - Žigimantas Pečiūra (Psichologija)
Starting a new position often brings significant stress. Amidst the adjustment to a new job, the increasing prevalence of gamification has revealed mixed effects on work-related factors, notably presenting an unclear impact on employee stress levels. Therefore, this article aims to explore the connection between gamification and occupational stress among new employees. The study involved 575 employees from various fields living in the United Kingdom or the United States who have been working in their new jobs for no longer than one year. The study utilized the Perceived Occupational Stress (POS) scale by Marcatto and colleagues (2021) and a questionnaire based on the GAMEFULQUEST model (Högberg, Hamari, and Wästlund, 2019) to evaluate the overall gameful experience in the work environment. Participants were also given descriptions of eight gamification elements and were asked to assess how frequently they encountered and engaged with these elements in their new roles. The obtained results showed that new employees’ limited interaction with gamification, marked by a low number of gamification elements, rare encounters, and low engagement, contributes to a prediction of higher stress experience. This trend was also observed with perceived challenges and competition in the workplace environment. Finally, gameful experiences related to guidance, social connectedness, accomplishments, and playfulness predicted lower stress scores.